1989
DOI: 10.1007/bf00114412
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of efficiency in the delivery of financial services: The case of life insurance agencies

Abstract: Scale and scope economies are examined for life insurance agencies that distribute multiple financial products. The results of this study suggest that there are significant administrative returns to scale for firms that sell a mix of financial products. The findings for scope estimates are inconsistent, suggesting that there are positive and negative cost complementaries for pairs of products. Subadditivity can be rejected, suggesting that joint distribution of financial products is not necessarily more effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…However, Houston and Simon(1970)thinks premium to insurers is what income to manufacturers, and therefore can be regarded as the indicator of output. Similar arguments appeared in: Praetz(1980); Fields and Murphy(1989); Grace and Timme (1992); Gardner and Grace (1993);Rai (1996);Diacon (2001);and Li (2005). They consider premium as an appropriate indicator of output, assuming the product is homogeneous and competitive pressures compel all insurers to charge the same price.…”
Section: Amount Of Labor (X2)supporting
confidence: 66%
“…However, Houston and Simon(1970)thinks premium to insurers is what income to manufacturers, and therefore can be regarded as the indicator of output. Similar arguments appeared in: Praetz(1980); Fields and Murphy(1989); Grace and Timme (1992); Gardner and Grace (1993);Rai (1996);Diacon (2001);and Li (2005). They consider premium as an appropriate indicator of output, assuming the product is homogeneous and competitive pressures compel all insurers to charge the same price.…”
Section: Amount Of Labor (X2)supporting
confidence: 66%
“…Evidence to date is mixed. In a sample of Canadian insurers, Bernstein (1992) found that significant savings occurred when producing multiple products, while Fields (1988) and Fields and Murphy (1989) found nothing to suggest that scope economies existed in the US industry. Alternatively, in a study of the US life insurance industry, Meador et al (2000, p. 189) concluded, 'these results provide evidence that life insurers offering a diversified product mix have achieved greater average X-efficiency than focused [life insurers]'.…”
Section: Specification Of Variablesmentioning
confidence: 91%
“…It was initially developed to compare the technical efficiency of public sector and not-for-profit production units (Charnes, Cooper et al, 1978), but, more recently, it has been applied successfully to the financial sector (Fields and Murphy, 1989;Ferrier and Lovell, 1990;Fields, Murphy et al, 1993;Nasser Katib and Matthews, 1999). It is therefore appropriate to the task of analysing the technical efficiency of pension subject to: In DEA, efficiency is defined as the ratio between a weighted sum of outputs and a weighted sum of inputs, where sets of weights for each of the observed production units are found by solving the following model proposed by Charnes, Cooper and Rhodes (1978), referred to as the CCR model (Boussofiane and Dyson, 1991):…”
Section: Efficiency Measurement and Datamentioning
confidence: 99%